'The living hand gives birth to the painter': Selected writings on painting by Lee Ufan. (1st October 2020) - Morley, Simon
Alongside his studio practice, the Korean artist Lee Ufan (b.1936) has consistently published writings that are intended to both elucidate his own practice and to address much broader issues relating to art and culture. Through his writing and art, Lee has sought the grounds from which to both assimilate and challenge Westernizing hegemony, based on a deep understanding of both East Asian and Western art and philosophy. Lees work maps the conventions of modernist Western abstraction onto traditional East Asian concepts of painting, most especially in relation to the role of the body, circulating energy, void and the 'untouched'. The selection below is a small sample of his writings, and they are preceded by an introduction to Lee Ufan, and a brief interview with the artist conducted by email with Simon Morley in 2017.